Interventions in Banks During Banking Crises : The Experience of Indonesia - Enoch, Charles (IMF Policy Discussion Papers; Policy Discussion Paper, 2000)
Interventions in banks are often an integral element of a government's program for addressing a systemic banking crisis. Interventions may be warranted because the banks are deeply insolvent or riddled with fraud; they may be requiring substantial liquidity support. In some circumstances closures may be more effective than open bank resolution. There were four major sets of bank closures in Indonesia between November 1997 and March 1999. The initial closures were subject to criticism, but the more recent ones were viewed more positively. This paper looks at these experiences, and draws conclusions about closing banks in a systemic crisis.